Sizing of boy's plus-sized crew neck shirts of selected local brands - Maldo, Iris Faye Loreto
The study sought to determine the plus-sizxe crew neck shirts' size range currently available in the market. The study is a descriptive survey where the merchandisers of selected brands were interviewed and were asked for the measurements of finished goods. Purposive sampling was utilized to choose suppliers of plus-size boy's crew neck shirts. Those who producer the XL, 2XL, 3XL sizes were included in this study to determine the size measurement specifications used by these companies. Measurement specifications given by the manufacturer were tabulated and the analysis of the variances from each of the measurement specification as obtained. The results show that each brand came up with their own way of developing size standards. They did not use actual representative body measurements for their size development. Instead, they based their measurements from finished garments. The actual body of the child was used to fit the finished garment and then the necessary revisions were made. Size grading was derived based on feedback from sales and customers. With the help of this study, brands can create a better fit for their shirts. It is also important that the brands ensure that the finished goods comply with the specified measurements. It has been noted that the declared size specification in some cases are not followed. After two decades, the Bureau of Product Standards must update their data and conduct another survey to set he body standards of Filipino children. These garment companies should have the current standards body measurement for better fit quality since children who fit the finished goods do not represent the standard body measurement of Filipino children. It is likely that the sizing standards are not correctly graded. Fit on one hand for plus-sizes are subjectively appreciated by these children.